Imaging cells and nanoparticles using modulated optically computed phase microscopy - Xuan Liu; Rupak Bhakta; Emily Kryvorutsky; Yuanwei Zhang (Scientific Reports)
Abstract Nanoparticles (NPs) have been successfully used as drug delivery systems. To develop and optimize NP-based drug delivery systems, it is essential to understand the dynamics of cell-NP interactions. Quantitative phase imaging techniques enable label-free imaging and have the potential to reveal how cells interact with NPs. To measure the subtle motion at cellular and subcellular scales, it requires a high phase sensitivity and a high spatial resolution. However, phase imaging techniques are limited by an intrinsic tradeoff between sensitivity and resolution. To overcome the tradeoff, we develop a technology termed as modulated optically computed phase microscopy (M-OCPM) based on low coherence interferometry and optical computation. The key innovation of M-OCPM is to utilize optical computation that performs Fourier transform of the interferometric spectra, imposes temporal modulation on the interference signal, and circumvents the sensitivity-resolution tradeoff. We evaluated the performance of M-OCPM using various samples, and demonstrated its label-free imaging capability, high sensitivity (nanometer scale displacement sensitivity) and high resolution (~ 250 nm). Particularly, we imaged NPs along with cultured cells and showed different signal characteristics for NPs that were adhered to the cells or in the cell culture medium. Our results clearly demonstrated the feasibility of M-OCPM in studying cell-NP interactions.